Marine species as safe source of LC-PUFA and micronutrients: Insights in new promising marine food in Peru - Loaiza I. (2020)
Seafood could be a promising way to supplement healthy fatty acids and trace elements to the Peruvian diet. Seafood from northern Peru was characterized with the highest relative concentrations of long-chain polyunsaturated fatty acids (LC-PUFAs), while in the center region marine species had the lowest As and Pb contents. Peruvian marine species are rich in LC-PUFAs and micro-nutrients (Cu, Fe, Mn, Zn), including species considered as potentially edible (e.g. Cycloxanthops sexdecimdentatus), but also non-edible species (e.g. Caulerpa filiformis). Nevertheless, it is crucial to consider toxic metals, e.g. As and Cd, which could pose a risk for consumers. High levels of beneficial LC-PUFAs and micro-nutrients would be taken up (up to 80% of the recommended values) when the Peruvian population would consume the estimated safe amount of seafood. Scoring species for fatty acid and metal content resulted in gastropods (e.g. Bursa ventricosa) as being the least beneficial species. © 2020 Elsevier Ltd